Is the canine corpus luteum an insulin-sensitive tissue?. Issue 3 (December 2016) - Sousa, Liza Margareth Medeiros de Carvalho; Silva, Renata dos Santos; Fonseca, Vanessa Uemura da; Leandro, Rafael Magdanelo; Di Vincenzo, Thiago Senna; Alves-Wagner, Ana Bárbara; Machado, Ubiratan Fabres; Papa, Paula de Carvalho
Abstract : This study aimed to determine in the canine corpus luteum throughout the dioestrus (1) the influence of insulin on glucose uptake; (2) the regulation of genes potentially involved; and (3) the influence of hypoxia on glucose transporter expression and steroidogenesis, after treatment with cobalt chloride (CoCl2 ). Glucose uptake by luteal cells increased 2.7 folds ( P < 0.05) in response to insulin; a phenomenon related to increased expression of glucose transporter (GLUT) 4 and phosphorylation of protein kinase B (AKT). The gene expression of insulin receptor and SLC2A4 (codifier of GLUT4) genes after insulin stimulation increased on day 20 post ovulation (p.o.) and declined on day 40 p.o. ( P < 0.05). Regarding potentially involved molecular mechanisms, the nuclear factor kappa B gene RELA was upregulated on days 30/40 p.o., when SLC2A4 mRNA was low, and the interleukin 6 ( IL6 ) gene was upregulated in the first half of dioestrus, when SLC2A4 mRNA was high. CoCl2 in luteal cell cultures increased the hypoxia-inducible factor HIF1A /HIF1A and the SLC2A4 /GLUT4 expression, and decreased progesterone (P4) production and hydroxyl-delta-5-steroid dehydrogenase 3 beta ( HSD3B ) mRNA expression ( P < 0.05). This study shows that the canine luteal cells are responsive to insulin, which stimulates glucose uptake in AKT/GLUT4-mediated pathway; that may be related to local activity of RELA and IL6. Besides, the study reveals that luteal cells under hypoxia activate HIF1A-modulating luteal function and insulin-stimulated glucose uptake. These data indicate that insulin regulates luteal cells' glucose disposal, participating in the maintenance and functionality of the corpus luteum.